Liraglutide demonstrates a therapeutic effect on mitochondrial dysfunction in human SGBS adipocytes in vitro - Vaittinen Maija; Ilha Mariana; Herbers Elena; Wagner Anita; Virtanen Kirsi A; Pietiläinen Kirsi H; Pirinen Eija; Pihlajamäki Jussi (Elsevier, 2025)
Aims
Liraglutide (LG), a glucagon-like peptide-1 receptor (GLP-1R) agonist, has been shown to improve white adipose tissue mitochondrial metabolism in mice but not in human adipocytes. Therefore, we explored whether LG has therapeutic efficacy in mitochondrial dysfunction in human adipocytes in vitro.
Methods
We tested the effects of short-term (ST-LG: 24 h) and long-term (LT-LG: D0-15 days) treatments in human SGBS adipocytes on mitochondrial respiration, mRNA and protein expression. GLP-1R inhibition was investigated by the co-treatment of GLP-1R inhibitor, exendin 9–39 (Ex9-39) and ST-LG treatment. We also explored the ability of ST-LG to alleviate mitochondrial dysfunction induced by tumor necrosis factor-alpha (TNFα).
Results
LT-LG treatment induced the formation of smaller lipid droplets and increased the expression of genes related to lipolysis. Both ST-LG and LT-LG treatments promoted mitochondrial respiration. Additionally, LT-LG treatment increased the expression of a brown adipocyte marker, uncoupling protein 1 (UCP-1), and the markers of mitochondrial biogenesis. Interestingly, ST-LG rescued TNFα-induced defects in mitochondrial energy metabolism and inflammation in SGBS adipocytes.
Conclusion
LG stimulates mitochondrial respiration and biogenesis in human adipocytes, potentially via UCP-1-mediated adipocyte browning. Importantly, our study demonstrates for the first time that LG has a therapeutic potential on mitochondrial activity in human adipocytes.